Sensitivity and specificity of the flexion and extension relaxation ratios to identify altered paraspinal muscles' flexion relaxation phenomenon in nonspecific chronic low back pain patients. (February 2023) - Gouteron, Anaïs; Tabard-Fougère, Anne; Moissenet, Florent; Bourredjem, Abderrahmane; Rose-Dulcina, Kévin; Genevay, Stéphane; Laroche, Davy; Armand, Stéphane
Abstract: Background: Among the main methods used to identify an altered flexion relaxation phenomenon (FRP) in nonspecific chronic low back pain (NSCLBP), it has been previously demonstrated that flexion relaxation ratio (FRR) and extension relaxation ratio (ERR) are more objective than the visual reference method. Objective: To determine the sensitivity and specificity of the different methods used to calculate the ratios in terms of their ability to identify an altered FRP in NSCLBP. Methods: Forty-four NSCLBP patients performed a standing maximal trunk flexion task. Surface electromyography (sEMG) was recorded along the erector spinae longissimus (ESL) and multifidus (MF) muscles. Altered FRP based on sEMG was visually identified by three experts (current standard). Six FRR methods and five ERR methods were used both for the ESL and MF muscles. ROC curves (with areas under the curve (AUC) and sensitivity/specificity) were generated for each ratio. Results: All methods used to calculate these ratios had an AUC higher than 0.9, excellent sensitivity (>90 %), and good specificity (80–100 %) for both ESL and MF muscles. Conclusion: Both FRP ratios (FRR and ERR) for MF and ESL muscles, appear to be an objective, sensitive and specific method for identifying altered FRP in NSCLBP patients.